An in-depth study on survival mechanism of bacterial isolates in disinfectants within the hospital environment - Rakshit, Pue; Singh, Aradhana; Singh, Ravindra; Banerjee, Tuhina (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe emergence of disinfectant resistance has become a severe threat due to reduced effectiveness. This study was undertaken to determine how bacteria adapt to survive exposure to disinfectants in the busiest section of a tertiary care hospital in Varanasi, India.MethodsFour isolates (two Klebsiella pneumoniae, Kp1 and Kp2; two Pseudomonas aeruginosa, Pa1 and Pa2) were obtained from chlorhexidine (CHX)–based handwash during microbiological surveillance of “in-use disinfectants” in hospital. Six disinfectants [4% CHX, 2% glutaraldehyde, 7.5% hydrogen peroxide, 1% sodium hypochlorite and 0.1% benzalkonium chloride (BAC), and 70% ethyl alcohol] were tested against these four isolates to determine minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Antibiotic profile, change in MIC on exposure to disinfectants and biofilm formation in the presence and absence of disinfectants was studied. Whole genome sequencing (WGS) was done to identify the resistance mechanisms.ResultThe isolates showed the highest MBC/MIC ratio (4) against glutaraldehyde. Exposure to supra-inhibitory concentration of BAC for 21 days resulted in doubling of MIC/MBC. The majority (75%) of the isolates were multidrug resistant. All the isolates were strong biofilm producers. The reduction rate of biofilm formation decreased with an increase in the concentration of disinfectants (p = 0.05 for BAC). WGS revealed multiple AMR genes including blaDIM-1, disinfectant-resistant gene and efflux pump genes.ConclusionThe study emphasized the various adaptation strategies of these isolates for survival in disinfectant environment, thus posing a huge challenge for their control in the hospital environment.